Development of a Precision Map of the Village Based using Drone Imagery to Improve the Quality of Planning - Prabowo, Gunawan; Bisri, Mohammad; Asmara, Rosihan; Budiyanto, Ari Sugeng; Suprapedi; Aziz, Abdul (Jurnal Pembangunan dan Alam Lestari, 2025)
Integrating drone technology into rural planning offers transformative advancements in geographic mapping by providing exceptional precision, efficiency, and accessibility. Traditional mapping methods often lack the granularity required to address the complexities of rural landscapes, leading to ineffective planning and resource allocation. This study develops a high-resolution precision map using drone imagery to enhance decision-making processes and promote sustainable development. A participatory approach involving local stakeholders ensures the alignment of spatial data with community priorities. This research aims to compare satellite and drone images in the planning stage; the spatial approach was used. The results highlight the superior accuracy of drone-based maps over satellite imagery, significantly improving land-use planning, infrastructure development, and environmental management. This approach aligns with Sustainable Development Goals (SDGs) 9, 11, and 15 by fostering community engagement and reducing post-planning corrections. The findings emphasize the critical role of precision mapping in optimizing resource allocation, minimizing disputes, and supporting participatory governance. Future studies are recommended to explore scalability, technological advancements, and applications in addressing global challenges such as climate change and urban-rural integration. Keywords: drone, mapping, participatory, precision, SDGs, sustainable, technology